2002
DOI: 10.1007/bf02723690
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carriage ofHaemophilus influenzae

Abstract: Multidrug resistant nasopharyngeal H. influenzae in young healthy children may act as reservoir. Monitoring of antibiotic resistance among nasopharyngeal H. influenzae as a surrogate for invasive H. influenzae seems an attractive option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…Population based studies of healthy children in India report asymptomatic carriage rates for Hib of 8% and recent data from West Bengal report rates of 6% in unvaccinated healthy children [15][16][17]. The prevalence of Hib colonization in this cohort was 13%.…”
Section: Discussionmentioning
confidence: 77%
“…Population based studies of healthy children in India report asymptomatic carriage rates for Hib of 8% and recent data from West Bengal report rates of 6% in unvaccinated healthy children [15][16][17]. The prevalence of Hib colonization in this cohort was 13%.…”
Section: Discussionmentioning
confidence: 77%
“…Numerous reports from different parts of the world describe the carriage rate to range between 3.5-77% for S. pneumoniae and 11.6-76% for H. influenzae (Arnold et al 1996;Chiou et al 1998;Principi et al 1999;Parry et al 2000;Talon et al 2000;Uraz et al 2000;Das et al 2002). In general, high carriage rates of S. pneumoniae and H. influenzae were detected in winter and during rainfall, in children under 2 years of age and in children of low socioeconomic status (Talon et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…No macrolide resistant H. influenzae isolates were reported from the UK, Germany, France and Italy (0%, Sahm et al 2000). Das et al (2002) reported 95.4% of H. influenzae isolates as erythromycin resistant. The highest prevalence of co-trimoxazole resistant H. influenzae is reported from India (30-80%) (IBIS study 1999;Nag et al 2001;Das et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the monitoring of nasopharyngeal H. infl uenzae as a surrogate marker for invasive and locally invasive H. infl uenzae seems an attractive option. 3 The present study was planned to (i) detect the carriage of BLNAR in nasopharynx of normal healthy school-going children, (ii) test the level of ampicillin resistance, and (iii) study the correlation of ampicillin resistance with resistance to other antimicrobials. In order to answer the pathogenic potential of H. infl uenzae, frequency of serotype b and biotypes I, II, and III among BLNAR H. infl uenzae was also estimated.…”
mentioning
confidence: 99%